The impact of acetylcholinesterase inhibitors on the extracellular acetylcholine concentrations in the adult rat brain: A meta-analysis - Noori, Hamid Reza; Spanagel, Rainer (Synapse, 2012)
In vivo microdialysis has become a key method in investigating the dynamics of different neurotransmitter systems such as acetylcholine in the extracellular fluid. Depending on the sensitivity of the analytical method applied for measuring acetylcholine levels in brain dialysates, acetylcholinesterase (AChE) inhibitors are often used to increase the basal acetylcholine level up to a detectable magnitude. This artificial manipulation of the system questions the outcome of pharmacological studies and has led to a large number of experiments pursuing the appropriate physiological and pharmacological concentration of the AChE inhibitors in a range between 0.01 and 100 μM. However, the complexity of the action of these substances, particularly through the involvement of muscarinic autoreceptors and the induction of an autoinhibitory effect on acetylcholine release, did not allow this quest to be resolved completely and suggests the application of advanced mathematical methods for the evaluation of acetylcholine baseline levels. Here we performed a meta-analysis on published datasets of in vivo microdialysis measurements to assess the concentration-dependent effects of various AChE inhibitors on acetylcholine levels within the prefrontal cortex, nucleus accumbens, caudate putamen, and hippocampus in adult rats. In total 3255 rats were analyzed and we found that when compared with the minority of studies (14%) that did not use AChE inhibitors (these studies yielded basal levels between 0.55 and 2.71 nM depending on the brain site) an up to 350-fold increase in baseline values after the application of an inhibitor could be detected. Especially, the derivates neostigmine bromide and physostigmine sulfate seem to produce dramatic effects. Furthermore, concentration-dependent effects after the application of AChE inhibitors could not be established. In the case of neostigmine bromide an inverted concentration (0.1-10 μM)-response relationship was even detected. We conclude that although the presynaptic action of AChE inhibitors is well understood the nonphysiological and concentration-independent augmentation of the acetylcholine system requires the use of a standard protocol in order to produce replicable and comparable results. Our meta-analysis suggests the use of 0.1 μM neostigmine which produces an approximately 10-fold boost of brain baseline levels. Synapse 2012. © 2012 Wiley Periodicals, Inc.